Outcomes of exposure to workplace bullying: A meta-analytic review - Nielsen, Morten Birkeland; Einarsen, Ståle (Work and stress, 2012)
This paper reports results from two meta-analyses of the potential individual-level outcomes of exposure to workplace bullying. After introducing a theoretical framework for the possible relationships between bullying and outcomes, Study 1 summarizes 137 cross-sectional effect sizes from 66 independent samples (N=77,721). The findings show that exposure to bullying is associated with both job-related and health- and well-being-related outcomes, such as mental and physical health problems, symptoms of post-traumatic stress, burnout, increased intentions to leave, and reduced job satisfaction and organizational commitment. Non-significant or weak associations were established for absenteeism, performance, self-perceptions, and sleep. Study 2 examines longitudinal relationships between bullying and mental health and absenteeism, respectively. Based on prospective associations from 13 samples (N=62,916), workplace bullying influenced mental health problems over time, while baseline mental health problems were associated with a similar increased risk of subsequent reports of exposure to bullying. The long-term effect of exposure to bullying on absenteeism was rather weak. To summarize, the two meta-analyses provide robust evidence for the detrimental effects of workplace bullying that are in line with the theoretical framework presented. The findings have implications for the development of strategies against bullying. Directions for future research are discussed.